Kajian Yuridis Tentang Batasan Kewenangan Pelaksana Tugas (PLT)/ Penjabat (PJ) Gubernur Ditinjau Dari Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintah Daerah - Nasrullah; Muhammad Ferdy Winata; M.Yamani (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
This study aims to analyze the problems in the Unitary State of the Republic of Indonesia where the highest power is held by the central government, but the territory of the Unitary State of the Republic of Indonesia is very large and divided into islands and archipelagos as well as large and small regions so that in exercising its power, the central government is obliged to hand over some of its authority to the regions, to regulate their respective regions. This study uses a normative approach with an analysis of the articles contained in Law Number 23 of 2014 concerning Regional Government. The results of the study indicate that there are problems in the Regional Government system, especially the Regional Head who is problematic, such as the Limitation of the authority of the Acting Head in carrying out his duties as the Regional Head comes from the mandate authority, where the authority of the Acting Regional Head is limited to carrying out authority in the form of policies that have been determined by the definitive Regional Head in the Regional Government because his position is only as a temporary official who replaces the vacancy of the Regional Head. The Acting Regional Head does not have the authority to issue decisions and/or actions that have legal impacts on the Regional Government organization. As well as the implementation of the appointment of the Acting (Pj) Regional Head when a vacancy occurs. However, the appointment mechanism is considered undemocratic and invites controversy. The importance of improving this mechanism to involve more community participation in the regional head election process. The effectiveness of the Acting Governor's position in the administration of government will not run optimally or will not be effective because there are limitations inherent in replacement officials such as acting governors (Plt) as stated in the legislation so that the urgency of the issue of appointing the Acting Governor in the Regional Government system still has pros and cons, whether it is democratic or political